Combined transcriptomic and metabolomic analyses reveal the mechanism of debagged 'Fuji' apple sunburn. (1st May 2023) - Feng, Yifeng; Liu, Li; Yu, Jing; Chen, Rongxin; Hu, Can; Wang, Hui; Li, Dongmei; Wang, Zidun; Zhao, Zhengyang
Abstract: Bagging of apples can improve the quality and commercial value of fruit. However, the sudden exposure of bagged fruit to high temperature and high light can lead to sunburn of the fruit surface. The molecular mechanism underlying the process of apple skin sunburn is poorly characterized. Here, we analyzed transcriptomic and metabolomic data from debagged apples subjected to high temperature and high light stress. Specifically, we studied the differential gene expression and metabolite accumulation in normal apple skin (NM), photooxidized apple skin (PS), and skin with browned (SB). High light and heat stress led to enrichment of differentially expressed genes (DEGs) related to the flavonoid biosynthesis pathway, and screening revealed 32 transcription factors (TFs) and 11 structural genes as targets. Furthermore, we found that MYB family TFs were significantly correlated with most structural genes in the flavonoid metabolism pathway, particularly the MdMYBR9 TF. We injected the MdMYBR9 TF into apple skin, and we found that the apple skin with overexpression of MdMYBR9 TF exhibited less severe sunburn, the apple with silenced MdMYBR9 TF exhibited severe sunburn. These findings provide a theoretical basis for further understanding the transcriptional regulation mechanism related to apple skin sunburn. Highlights: Combined omics study reveal the molecular mechanism of apple peel sunburn. Sunburn led to enrichment of differentially expressed genes (DEGs) related to the flavonoid biosynthesis pathway. The key transcription factor (TF) MYBR9 in flavonoid biosynthesis pathway was screened. The apple skin with overexpression of MdMYBR9 TF exhibited less severe sunburn.